La localización espacial de la contaminación en la Quinta Región - Quintanilla, Víctor G. (Investigaciones Geográficas: Una mirada desde el sur, 2014)
This investigation presents the spatial localization to the main contamination types and their influence over an area to the Middle Chile between the parallel 32° y 34° Lat. S. In this region the geographic zone more affected are: the coastal zone, the Marga-Marga creek basin and the Aconcagua river basin. The urban and industrial contamination are the main pollution in Middle Chile, fundamentally owing to the vigorous demographic concentration in this place. The chilean poublic and comunal organism are very interest inorder to control this pollution types.